Polish spoken language and Belarusian dialects in Lithuania. : Preliminary considerations on selected areal aspects - Jankowiak, Mirosław (Theoria et Historia Scientiarum, 2025)
Research on the Polish language in Lithuania has a long tradition. Halina Turska made the first area division in the 1930s. In general, most researchers of Lithuanian Polish refer to this division to this day. This division was made based on selected phonetic and grammatical features, on the one hand, differentiating them from the standard Polish language, and on the other, three areas from each other (the Vilnius area, the Kaunas area, and the Smalvos area). In the 1990s, new areas for the Polish language in north-western Belarus were defined by I. Grek-Pabisowa (mainly based on the frequencies of selected features). Over the course of over 30 years, a vast amount of material has been collected in the form of interviews recorded in Lithuania, north-western Belarus, and Latvia which allows analyzing new aspects, including areal issues. On the one hand, these are recorded interviews in Polish, on the other hand, in the Belarusian dialect. Conducting field research in Lithuania since 2009, I have collected over 130 hours of Belarusian dialects and several hours of Polish. The preliminary analysis of the material showed many features common to Belarusian dialects and Lithuanian Polish, covering specific areas.